The Significance Of Sulh In The Syariah Court - Nur Syasya (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2020)
Sulh is a form of alternative disputes resolution (ADR) in the context of Islamic law. Due to the increasing rates of divorces, family conflicts and custody claims, the Syariah Court made a decision in introducing a tributary channel in the legal system that allows people to negotiate and reach an amicable agreement and settlement without court intervention, which is known as Sulh.It will be a good platform for disputants to settle things accordingly without having to wait for a period of time. Thus, It acts as a catalyst in processing cases and resolving disputes among disputants. However, there are still numbers of people who do not know the existence of Sulh and its significance. This is due to the lack of exposure, knowledge and the term itself “Sulh” in arabic makes it even harder to be understood among people whom are not well-versed in arabic language. As a result, people are restricted to one court-assisted method when there’s actually more tributaries to the problem-solving. Although it is an ancient method but it is efficient in a way it offers disputants a win-win situation and satisfactions. Having said that,this paper will further explain the history of Sulh, the significance of its application and practice in the decision-making as a way forward in resolving marriage conflicts or family matters. Furthermore, this paper employs a qualitative approach and the data collection will be based on library and documentations.Hence,the findings of this paper is based on the literature reviews and past studies’ of previous researchers on Sulh.